Satureja : Ethnomedicine, phytochemical diversity and pharmacological activities /: Ethnomedicine, phytochemical diversity and pharmacological activities. (2016) - Saeidnia, Soodabeh; Gohari, Ahmad Reza; Manayi, Azadeh; Kourepaz-Mahmoodabadi, Mahdieh
No abstract available